Unprecedented experience of teaching direct and indirect restorative procedures through the Zoom platform using custom model in times of COVID-19. - Saravia-Rojas, Miguel Á. (2022)
COVID-19 and the continuity of the health emergency have led to the maintenance of social distancing and care in the capacity of public spaces during 2021. This continues to cause attendance at classes to be affected, forcing higher education institutions to continue their activities remotely. The dentistry career is eminently practical, in that sense many courses had to experience an adaptation to this new contingency. This article presents the adaptations, strategies and methodologies in two eminently clinical career courses that are taught in the sixth and seventh cycle of the dentistry career of the Faculty of Dentistry of the Cayetano Heredia Peruvian University, called Integral Adult Clinic. III and Integral Clinic for Adults IV, which are taught in the first and second semesters of each year. It shows how these courses were carried out using the Zoom platform remotely simulation custom model (Manenquin-UPCH) with the aim of carrying out the acquisition of skills by the students. This is an unprecedented experience never before described to date.